Improvement in soil quality through tillage and residue management in Jute (Corchorus spp.) based cropping systems of Indo-Gangetic plains. Issue 1 (2nd January 2022) - Saha, R.; Paswan, Alka; Mazumdar, S. P.; Barman, D.; Majumdar, B.; Behera, M. S.; Saha, A. R.
Abstract: The changes in soil quality in terms of carbon accumulation, aggregate stability and enzyme activity were evaluated in Jute based cropping systems (jute-rice-wheat, jute-rice-lentil and jute-rice-mustard) subjected to various tillage systems, i.e. conventional tillage (CT), no tillage (NT) and no tillage with additional crop residue retention (NTR) under tropical climate of Indo-Gangetic plains. The crops were grown with conventional (disc plowing, followed by 2 cultivators) and no tillage (no ploughing) and additional crop residues were applied as Sesbania spp. with a rate of 2 t ha −1 . Addition of crop residue under no tillage improved bulk soil organic carbon (SOC), particulate SOC content (PSOC) and aggregate stability, promoting a better soil physico-chemical behavior in all crop-rotations. The SOC contents under No tillage with residue incorporated plots (NTR) are much higher, maximum being in jute-rice-lentil (6.02 and 7.29 g kg −1, respectively in 0–0.15 and 0.15–0.30 m soil depth). The highest SOC density (330.03 g C m −2 ) and stock (3.30 Mg C ha −1 ) were recorded in the NT R. Soil microbial biomass (SMBC) was significantly higher in NT R (range: 641.84 to 745.97 µg g −1 ) followed by NT (631.42 to 678.46 µg g −1 ) and CT (490.68 to 634.83 µg g −1 ). Jute equivalent yield (JEY) was highest in jute-rice-lentil (J-R-L) under NTR (7.33 t ha −1 ). Thus, no tillage with residue incorporation under Jute-rice-lentil system is highly beneficial in maintaining crop productivity and improving soil quality.